(3OjhGf eMeO LhGOs - (3eMeO LhGO Hf YHO GdQVG GdHZOGOj,J (B1170 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3agPg ofHPI ef fXe GdabjQ GdQGLj Yah QHg hGdQVG, eMeO LhGO Hf YHOGdQVG, GKHJgG NTjI GdVjGY s
(3BNQgG (B:s
(3hegeG JLO ddpNd YjHkG ahGQg hcf jG QVG Yf YjHg eJZGVjG aYjf GdQVG Yf cd YjH cdjdI ceG Cf Yjf GdSNW JHOj GdeSGhjG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B302s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B201 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI HGdfLa (B(30) s
Keywords: (3GdCOHs